Ethnography among ‘experts’: notes on collaboration and sabotage in the field - Gil, Gaston Julian (2010)
Based on an analysis of how an ethnographic research project was received by ´experts´ in the field, a series of reflections will be put forward on ethnographic fieldwork and some aspects of anthropological knowledge. Developed on the assumption that the vicissitudes of ethnographic practice are central to the process of knowing the ´Other´, this reflexive exercise focuses on how informants may turn into either the ethnographer´s saboteurs or his/her contributors -and even co-authors. As spaces in the academic arena are shared -and somehow disputed- extremely conflictive relationships spring raising fears in the ethnographer, who may suffer direct sabotages in his experience on the field.